การประเมินโครงการระบบโครงข่ายการเรียนรู้ไร้พรมแดน โรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 - บุบผามาศ, ชนัดดา (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 26 No 2 (2558): Academic Services Journal, Prince of Songkla University, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ประเมินโครงการระบบโครงข่ายการเรียนรู้ไร้พรมแดน โรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 โดยใช้รูปแบบการประเมิน CIPP Model ของ สตัฟเฟิลบีม ในการประเมิน 4 ด้าน ได้แก่ ด้านบริบท (Context) ด้านปัจจัยนำเข้า (Input) ด้านกระบวนการ (Process) และด้านผลผลิต (Product) รวมทั้งประเมินด้านผลกระทบ (Impact) ร่วมด้วย 2) ศึกษาแนวทางการพัฒนาโครงการระบบโครงข่ายการเรียนรู้ไร้พรมแดน โรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 โดยใช้การวิจัยแบบผสมผสาน (Mixed Method Research) ทั้งในเชิงปริมาณและเชิงคุณภาพ โดยข้อมูลเชิงปริมาณเก็บข้อมูลจากแบบสอบถามจากกลุ่มตัวอย่างของผู้บริหารสถานศึกษา จำนวน 219 คน ครูผู้สอน จำนวน 6 คน และนักเรียน จำนวน 373 คน ที่ได้มาจากการสุ่มตัวอย่างแบบหลายขั้นตอน (Multi-Stage Random Sampling) โดยการแบ่งโรงเรียนเป็น 3 ประเภท แล้วสุ่มตัวอย่างแบบง่ายและกำหนดขนาดกลุ่มตัวอย่างโดยการคำนวณจากตารางสำเร็จรูปของเครจซี่และมอร์แกน และข้อมูลเชิงคุณภาพเก็บข้อมูลจากการสัมภาษณ์ผู้เชี่ยวชาญจากสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 จำนวน 4 คน ผู้บริหารสถานศึกษา จำนวน 6 คน และครูผู้ดูแลระบบ จำนวน 6 คน และการสนทนากลุ่มของผู้บริหารสถานศึกษา จำนวน 3 คน และครูผู้ดูแลระบบ จำนวน 3 คน ที่ได้มาจากการเลือกแบบเจาะจง (Purposive Selection) วิเคราะห์ข้อมูลโดยใช้ค่าร้อยละ (%) ค่าเฉลี่ย (X_) ส่วนเบี่ยงเบนมาตรฐาน (S.D.) และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1. ผลการประเมินโครงการระบบโครงข่ายการเรียนรู้ไร้พรมแดน โรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 ในภาพรวมมีความเหมาะสมอยู่ในระดับมาก เมื่อพิจารณาผลการประเมินแต่ละด้าน พบว่า 1) ด้านบริบท มีความเหมาะสมในระดับปานกลาง โดยวัตถุประสงค์ของโครงการมีความเหมาะสมที่สุดและควรปรับปรุงด้านการติดต่อประสานงาน 2) ด้านปัจจัยนำเข้า มีความเหมาะสมในระดับมาก โดยความถูกต้องครบถ้วนและทันสมัยของบทเรียนมีความเหมาะสมที่สุดและควรปรับปรุงด้านงบประมาณการเบิกจ่าย 3) ด้านกระบวนการ มีความเหมาะสมในระดับมาก โดยการพัฒนาบุคลากรในโรงเรียน มีความเหมาะสมที่สุดและควรปรับปรุงด้านการนิเทศ กำกับ ติดตาม การดำเนินงาน 4) ด้านผลผลิต มีความเหมาะสมในระดับมาก โดยความรู้ความเข้าใจในการบริการด้านบทเรียน มีความเหมาะสมที่สุดและควรปรับปรุงด้านความพึงพอใจในการเข้าใช้งาน และ 5) ด้านผลกระทบ มีความเหมาะสมในระดับมาก โดยครูผู้สอนสร้างสรรค์สื่อการสอนที่หลากหลายมีความเหมาะสมที่สุดและควรปรับปรุงด้านความพึงพอใจของผู้ใช้งาน 2. แนวทางการพัฒนาโครงการระบบโครงข่ายการเรียนรู้ไร้พรมแดน โรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 พบว่า 1) การติดต่อประสานงานควรเป็นไปอย่างต่อเนื่องและมีแนวทางที่ชัดเจน 2) งบประมาณ วัสดุอุปกรณ์ และสถานที่ ควรจัดหาให้เพียงพอกับความต้องการโดยเทียบกับปริมาณขนาดของโรงเรียนแต่ละแห่งและควรมีการดำเนินการเบิกจ่ายอย่างรวดเร็ว 3) การนิเทศ กำกับ ติดตาม ควรเป็นไปอย่างต่อเนื่องและมีการดูแลอย่างใกล้ชิด 4) การเข้าใช้งานในระบบควรเป็นไปอย่างสะดวก รวดเร็ว โดยควรมีการพัฒนาระบบเครือข่ายอินเทอร์เน็ตให้ทั่วถึง เชื่อมต่อง่าย และ 5) การสร้างแรงจูงใจในการใช้งานควรเปิดเวทีนำเสนอผลงานและควรมีการให้รางวัลสนับสนุน คำสำคัญ: การประเมินโครงการ, การเรียนรู้ไร้พรมแดน   The purposes of this research were: 1) To evaluate a Boundless Learning Network System Project of schools under the jurisdiction of the Secondary Educational Service Area Office 8 by using the CIPP Model of Stufflebeam. The evaluation covered 4 aspects: the context, the input, the process and the product and the impact evaluation with the project. 2) To establish guidelines for the development of a Boundless Learning Network System Project of schools under the jurisdiction of the Secondary Educational Service Area Officed 8 by using Mixed Method research to collect both qualitative and quantitative data. Quantitative data were collected through a questionnaire survey of a sample group of 6 administrators, 219 teachers and 373 students selected by using Multi-Stage random sampling. The schools are divided into three categories by Simple Random Sampling and the sample size is determined by the calculation from Krejcie & Morgan’s ready–made table. Qualitative data were collected through an interview of 4 experts of the Secondary Educational Service Area Officed 8, 6 administrators and 6 teachers in charge of the system control. This sample group was selected by using the purposive selection. All the data were analyzed by percentage (%), mean (X_), standard deviation (S.D) and content analysis. The results of this research were as follows: 1. The evaluation of the project of the Boundless learning Network Systemof schools under the jurisdiction of the Secondary Educational Service Area Office 8 as a whole revealed that the appropriateness of the project was at a high level. Considering through each aspect, it was found that 1) The context of the project was appropriate at a medium level. The objectives of the project were the appropriate at the highest level while the scope of co-ordination needed improvement. 2) The input of the project was appropriate at a high level. The accurate and up-to-date lessons were appropriate at the highest level while the budget reimbursement needed improvement. 3) The process of the project was appropriate at a high level. School Personnel development was appropriate at a high level while supervision and monitoring needed improvement. 4) The product of the project was appropriate at the high level. The understanding of the lessons provision service was appropriate at the highest level while the satisfaction of the system accessibility needed improvement. 5) The impact of the project was appropriate at a high level. Teachers, various creative teaching media were appropriate at the highest level while the satisfaction of the users needed improvement. 2. Considering the guidelines to develop the Boundless Learning Network System Project of Schools under the jurisdiction of the Secondary Educational Service Area Office 8, it was found that. 1) The co-ordination process should be consistent and continuous and should have clear guidelines. 2) Budget, equipment, facilities and working offices should be provided to meet the requirements and appropriate to the school size. Budget reimbursement should be within a specified time limit. 3) Supervision and monitoring should be consistent and closely monitored. 4) The system accessibility should be easy and fast to access. The internet network should be updated widely and easy to connect. 5) Motivation should be provided. There should be a platform to be a showcase of work presentation and a reward should be offered. Keywords: project evaluation, learning network system